Construction of ZnCo2O4/Ag3PO4 composite photocatalyst for enhanced photocatalytic performance - Jiayi Liu; Jiafeng Hu; Hao Hu; Xiaotao Zhou; Qiwei Wang; Weizhi Wei; Wenhui Liu (Micro & Nano Letters)
Abstract In this study, ZnCo2O4/Ag3PO4 composite catalyst was prepared by the precipitation method, and their performance in the photocatalytic degradation of methyl orange (MO) was studied. The catalysts were characterized by scanning electron microscopy, high‐resolution transmission electron microscopy, X‐ray diffraction, energy‐dispersive X‐ray spectroscopy, selected area electron diffraction, X‐ray photoelectron spectroscopy, and UV‐Vis diffuse reflectance spectroscopy. The results indicate that the 0.1 ZnCo2O4/Ag3PO4 composite system has good photocatalytic activity in the degradation of methyl orange. Under simulated sunlight conditions, the degradation rate can reach 94% after 30 min. The maximum reaction rate constant of 0.1 ZnCo2O4/Ag3PO4 was 0.05301 min−1, which is 3 times and 52 times the rate constant of pure Ag3PO4 and pure ZnCo2O4, respectively. In catalyst recycling experiments, 0.1 ZnCo2O4/Ag3PO4 still degraded methyl orange at a rate of 84.4% after three cycles. Trapping experiments showed that holes and superoxide radicals mostly contributed to the photocatalytic degradation of methyl orange by the catalyst, while hydroxyl radicals played a partial role. The energy level structure of ZnCo2O4/Ag3PO4 is conducive to the effective separation of photogenerated electrons and holes, improving the lifespan of photogenerated charges. In the investigated catalyst series, 0.1 ZnCo2O4/Ag3PO4 demonstrated the best photocatalytic performance.